2016
DOI: 10.1021/acssensors.6b00532
|View full text |Cite
|
Sign up to set email alerts
|

Unique Sensing Interface That Allows the Development of an Electrochemical Immunosensor for the Detection of Tumor Necrosis Factor α in Whole Blood

Abstract: Electrochemical affinity biosensors that can operate in whole blood are a rarity because biofouling of electrode surfaces compromises the performance of the final device. The common anti-biofouling layers that can be applied to electrodes, poly­(ethylene glycol) (PEG) or oligo­(ethylene glycol) (OEG) layers, form a high impedance layer on the electrode, effectively passivating the electrode. In response to this issue, we have developed effective anti-biofouling chemistry, that employs short chain zwitterionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 44 publications
0
80
0
1
Order By: Relevance
“… 3 29 This enhanced performance of our serum neuronal exosome test across samples collected at multiple sites is at least in part due to our improved immunocapture assay using zwitterionic coating, a surface that resists non-specific binding. 30 Although exosomal α-synuclein per se was not sufficiently sensitive and specific to be used as a diagnostic marker, we show that this readout is consistent when tested across PD populations from three countries and stable over disease progression when assessed within individuals suggesting that it could be considered as a pharmacodynamic biomarker for α-synuclein targeting therapies in PD. Together with previous work in Alzheimer’s disease (AD), 31 32 our findings demonstrate that protein cargoes in L1CAM-positive extracellular vesicles exhibit distinct composition in neurodegenerative diseases that predate the clinical phase and offer a promising means to develop blood-based predictive markers of the relevant brain pathology.…”
Section: Discussionmentioning
confidence: 69%
“… 3 29 This enhanced performance of our serum neuronal exosome test across samples collected at multiple sites is at least in part due to our improved immunocapture assay using zwitterionic coating, a surface that resists non-specific binding. 30 Although exosomal α-synuclein per se was not sufficiently sensitive and specific to be used as a diagnostic marker, we show that this readout is consistent when tested across PD populations from three countries and stable over disease progression when assessed within individuals suggesting that it could be considered as a pharmacodynamic biomarker for α-synuclein targeting therapies in PD. Together with previous work in Alzheimer’s disease (AD), 31 32 our findings demonstrate that protein cargoes in L1CAM-positive extracellular vesicles exhibit distinct composition in neurodegenerative diseases that predate the clinical phase and offer a promising means to develop blood-based predictive markers of the relevant brain pathology.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, use of such long‐chain self‐assembled monolayers on electrodes is not desirable in the case of electrochemical approaches due to the formation of a high impedance layer on the surface, which can prevent the Faradaic electrochemistry of occurring at the underlying electrode . An alternative to OEG and PEG that has emerged recently is use of zwitterionic molecules containing phosphorylcholine moiety ,, . Studies have shown that an exquisite antifouling layer with very low impedance could be obtained by modifying glassy carbon and ITO electrodes with diazonium salt derived from phenylphosphorylcholine ,.…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al [19] described an electrochemical immunosensor for detection of tumor necrosis factor α (TNF-α) with a strategy to avoid non-specific adsorption. For this purpose, they used an original layer of phenylphosphoryl choline (PPC) and phenylbutyric acid (PBA).…”
Section: Discussionmentioning
confidence: 99%